Detection of changes in genes related to antioxidant and biotransformation function in broiler birds fed aflatoxin by real time PCR - SRIDHAR, MANPAL; THAMMIAH, VANDANA; SUGANTHI, R U (The Indian Journal of Animal Sciences, 2014)
Current findings suggest that the AFB1 failed to influence hepatic gene expression of SOD, CAT, EH, GPx and GST-α but increased the gene expression of the two biotransformation genes CYP1A1, and CYP2H1 at the levels used. Results show that changes in genes related to antioxidant and biotransformation function could be detected by real time PCR. Further work to study the expression of antioxidant and biotransformation genes with higher levels of aflatoxin along with beneficial effects of phytochemicals in amolerating the same in broiler birds are under progress.